Francisco de Sousa y su ‘oriente conquistado’ - Romo, Eduardo Javier Alonso (2011)
The present paper examines the book of the Jesuit Francisco de Sousa (1649-1712), missionary and historian Brazilian- Portuguese-Indian. It treats itself of the Oriente conquistado a Jesu Cristo pelos Padres da Companhia de Jesus da Provincia de Goa (Lisbon 1710). After outlining the figure of the author, we analyze different aspects of the book like his object and structure, the used sources, the genres included in him, the historical and social testimony of his time, as well as his later receipt.--- Original in Spanish.